Inhibition modulated by self-efficacy: An event-related potential study - Shi, Hong (Frontiers in Psychology, 2022)
Inhibition, associated with self-efficacy, enables people to control over thought and action and inhibit disturbing stimulus and impulsion and has certain evolutionary significance. This study analyzed the neural correlates of inhibition modulated by self-efficacy. Self-efficacy was assessed by using the survey adapted from the Motivated Strategies for Learning Questionnaire. Fifty college students divided into low and high self-efficacy group participated in the experiments. Their ability to conduct inhibitory control was studied through Go/No-Go tasks. During the tasks, we recorded students’ brain activity, focusing on N2 and P3 component in the event-related potential (ERP). Larger No-Go N2 amplitudes for high self-efficacy group were found compared with low self-efficacy group. Conflict detection was modulated by self-efficacy whereas conflict inhibition was not modulated by self-efficacy. The high self-efficacious students were capable of detecting conflicts but not necessarily followed by inhibition of the action operation. Taken together, these findings offer neurophysiological evidence to the important regulatory role of self-efficacy in inhibitory control ability development.